STRUCTURAL DAMAGE DETECTION BASED ON THE EXCITATION POINTS OPTIMIZATION AND ENERGY OF SIGNALS - LIU ManDong; PENG ZhenRui (Jixie qiangdu)
In order to effectively excite the local vibration mode of the structure,analyze response information and identify the damage,a structural damage detection method is constructed based on the excitation points optimization and energy of signals at different damage states. Firstly,the dynamic model of the structure is established and used to calculate the modal shapes,and then the minimum value of non-diagonal elements of MAC matrix is used as the fitness function. Modified particle swarm optimization（ MPSO） is used to optimize the number and position of excitation points,and evaluate of different excitation points arrangement schemes by MAC non-diagonal mean value and root mean square（ RMS） criterion. Then,the corresponding position of the truss test model is excited,and the time-domain signal energy at the measuring point before and after the damage is calculated,so as to identify the damage position and damage degree of the structure according to its relative change. In addition,the method can still identify the damage position and damage degree of the structure after Gaussian white noise with the signal-tonoise ratio of 10 dB is added to the signals at different working conditions. The experimental results verify the feasibility of the method.